2023
DOI: 10.1111/cen.14939
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid fine‐needle aspiration with parathyroid hormone washout as a preoperative localisation of parathyroid adenoma—A retrospective study

Pinchas Klein,
Shibli Alsleibi,
Ohad Cohen
et al.

Abstract: Objective: The use of parathyroid lesion aspiration in preoperative adenoma localisation is controversial. Concerns have been raised regarding both immediate safety (hematoma, infection, alterations on a subsequent histologic preparate) and long-term safety (seeding).We aimed to evaluate the short-and long-term safety, and the efficacy, of parathyroid fine-needle aspiration with parathyroid hormone washout as a localisation modality of parathyroid adenoma in patients with primary hyperparathyroidism.Design: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Although there is a consensus on the effectiveness of traditional imaging techniques, an ongoing debate surrounds the use of PFNA with PTH washout for the preoperative localization of parathyroid adenomas. [ 10 ] Immediate safety concerns associated with P-FNA, such as hematoma formation, infection risk, and potential alterations in histological examination, along with long-term risks such as cell spread and seeding, have been critically evaluated in recent studies. [ 10 ] Güneş et al [ 11 ] and Wenbo et al [ 12 ] highlighted the reliability of PTH washout in identifying parathyroid lesions, particularly in preoperative settings and in patients with negative preoperative sestamibi scans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is a consensus on the effectiveness of traditional imaging techniques, an ongoing debate surrounds the use of PFNA with PTH washout for the preoperative localization of parathyroid adenomas. [ 10 ] Immediate safety concerns associated with P-FNA, such as hematoma formation, infection risk, and potential alterations in histological examination, along with long-term risks such as cell spread and seeding, have been critically evaluated in recent studies. [ 10 ] Güneş et al [ 11 ] and Wenbo et al [ 12 ] highlighted the reliability of PTH washout in identifying parathyroid lesions, particularly in preoperative settings and in patients with negative preoperative sestamibi scans.…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] Immediate safety concerns associated with P-FNA, such as hematoma formation, infection risk, and potential alterations in histological examination, along with long-term risks such as cell spread and seeding, have been critically evaluated in recent studies. [ 10 ] Güneş et al [ 11 ] and Wenbo et al [ 12 ] highlighted the reliability of PTH washout in identifying parathyroid lesions, particularly in preoperative settings and in patients with negative preoperative sestamibi scans. However, potential risks associated with the procedure, such as inflammatory responses, parathyroid abscesses, and hematoma, have also been documented.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to the mentioned pre-operatory imaging methods was proposed to be ultrasound-guided parathyroid fine-needle aspiration (with PTH washout), but so far, there are not so many large studies to address this issue, which is not conventionally approved in many centres [55]. However, one study from 2023 showed a similar positive predictive value with 99m-Tc sestamibi scintigraphy; thus, it might become a first-line imaging modality in a selective subgroup of subjects with PHP [56].…”
Section: Concordance Of Pre-operatory Localisation Studies In Phpmentioning
confidence: 99%